Production sharing and Singapore's global competitiveness - Sven W. Arndt (Claremont McKenna College, Department of Economics, 2003)
This chapter investigates the contribution of cross-border production networks to the international competitiveness of a nation's producers. Cross-border sourcing of components has effects on productivity and efficiency that are very similar to those of technical progress. When a country's comparative advantage varies across the components of a product, the ability of that product to compete in world markets is improved when components are sourced from lowest-cost suppliers. Parts, components, and accessories play an important role in Singapore's trade with both less and more advanced countries. This opens opportunities as well as risks.
Keywords: 330; Lohnfertigung; Internationale Arbeitsteilung; Internationaler Wettbewerb; Singapur